The Theatre of Revolution Transforms Spectators into Political Actors: Performance as Political Engagement in the Transnational Counterculture - Andrew Hannon (European Journal of American Studies)
How can we resist the spectacle? This history explores actors and activists who found tools in avant-garde theatre and the underground press, drawing on the shared bonds of culture to resist the pacifying effects of the spectacle and turn it against itself. From the San Francisco Diggers, the theory and techniques of transforming passive spectators into political life actors were carried to England though the pages of popular reporting on the counterculture. Like a Trojan horse in popular culture, these techniques for activism were smuggled under what appeared to be a passive, voyeuristic gaze upon youth culture. In England, the Diggers and their ideas were embraced and celebrated by OZ Magazine and the burgeoning London hippie scene. This led to the founding of the Hyde Park Diggers and a return to England of a radical participatory call to action and a movement away from passive spectatorship. In the reservoir of English radical folk history and the contemporary innovations of avant-garde performance arts was found a powerful technique for resisting becoming a society of mere spectators.